ENGLISH-INTERNATIONAL HUMANITARIAN LAW IN A SHARIA DOMNINATED ISLAMIC CONTEXT: ARMED CONFLICT IN PAKISTAN - Faiz Bakhsh; Samza Fatima; Muhammad Bilal (دی اسکالر)
The applicability of International Humanitarian Law (IHL) to the non-international armed conflicts is questioned due to various reasons, mainly the complex nature of such conflicts fulfilling the criteria set under IHL. Firstly, states hesitate to acknowledge the existence of non-international armed conflicts by considering them as internal disturbances. Secondly, the complex nature and varying circumstances of such conflicts make their assessment very hard due to the multiplicity of the factors involved in the fighting. The armed conflict in Pakistan provides even more complex situations of such type of armed conflict where Sharia plays a vital role in the domestic legal structure of the state as well as other group fighting against claims being a true follower of Sharia, the application of IHL becomes even more critical in such a situation. The conflict in the former Federally Administered Tribal Areas (FATA) and surrounding areas of Pakistan between the state forces and Tehrik-e-Taliban Pakistan (TTP) led armed groups have been acknowledged as a non-international armed conflict after a long period by the government of Pakistan. This paper investigates the applicability of IHL to this conflict mainly on the doctrinal aspects of the study by interpreting and applying the relevant rules of IHL relating non-international armed conflicts through analysing the conflict in Pakistan under the said criteria and also looks at the social context of the study by looking at the obligation of the rules of IHL by both the parties belonging to a Sharia dominated social context. The doctrinal analyses of rules of IHL and the assessment of the conflict in Pakistan against the criteria set by IHL leads to a point where conflict in Pakistan is considered a non-international armed conflict, whereas the obligation of the rules of IHL has been observed on the lower side not due to the presence of Sharia dominated social context but due to various other reasons that occur during such type of conflicts all over the world.